A novel method to measure dual-task capacity in young football players: a preliminary study - Uysal, Ö.; Güzel, N. A.; Bayrakci Tunay, V.; Firat, T. (Journal of Athletic Training, 2024)
Context When deciding to return to sport, in the literature, evaluations based on physical abilities have usually been used. However, in the current literature, we have been urged to use more than physical performance evaluations. Classical dual-task testing methods do not simulate in-game loads and cannot sufficiently measure football players` dual-task capacity.